Listening to Country: a prison pilot project that connects Aboriginal and Torres Strait Islander women on remand to Country. Issue 2 (3rd April 2022) - Marchetti, Elena; Woodland, Sarah; Saunders, Vicki; Barclay, Leah; Beetson, Bianca
ABSTRACT: Research shows that prison programs addressing intergenerational trauma and grief, loss of culture and spiritual healing are necessary for incarcerated Aboriginal and Torres Strait Islander peoples. Indigenous-led or culturally focused programs receive little attention and limited resourcing in Australia's prison system compared with mainstream rehabilitation programs. Depending on the jurisdiction and prison, such programs can be even less accessible for Aboriginal and Torres Strait Islander women. Listening to Country was an arts-based prison pilot project that was developed by and delivered to Aboriginal and Torres Strait Islander women in the Brisbane Women's Correctional Centre. It aimed to explore the role of acoustic ecology, soundscape and deep listening in connection to culture and Country. This article presents findings from a process evaluation of that pilot project in order to illustrate the potential for Indigenous-led, culturally focused and culturally safe prison programs to improve wellbeing for incarcerated Indigenous peoples.